ANALISIS KORELASI KESEHATAN MENTAL DAN INDEKS PRESTASI MAHASISWA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI JAKARTA DENGAN KOMBINASI METODE XGBOOST DAN SHAP - zulfa, Eva; Amir, Hafniza; Ginting, Riskon; Sudarno, Sudarno (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
Mental health is a state of mental well-being that allows people to cope with life's pressures, realize their abilities, learn well and work well. According to UNICEF Indonesia, there are several conditions that affect a person's mental health, including anxiety, depression, panic, and stress. In the context of higher education, students are one of the components that fall into the adolescent age range who are often faced with mental health problems. Therefore, it is important to discuss in more depth the impacts caused by students' mental health. This problem prompted this study to analyze the correlation of students' mental health with their academic results on campus. This study focuses on the analysis of the correlation between mental health and the Student Achievement Index (IPK) of Business Administration students from the Jakarta State Polytechnic (PNJ). The method used in this study is a combination of XGBoost (eXtreme Gradient Boostin g) and SHAP (Shapley Additive Explanations). The combination of XGBoost and SHAP will create a regression model with several predictor variables which then determine the correlation weight of the predictor variables with the response variable. The purpose of this study is to prove the correlation of these two things with several mental health disorder instruments, namely feelings of anxiety, depression, panic and stress. This study is expected to be a policy reference for PNJ leaders in determining the priorities and focus of policies related to the mental and academic health of their students. This study uses the Superior Basic Research scheme for Higher Education (PDUPT) and has outputs in the form of publication of articles in reputable international journals or articles in accredited sinta journals 1-2 or patents/simple patents or reference books with ISBNs, and reputable indexed international seminar articles.